Xerostomia in Geriatric Population: An Insight into Etiopathogenesis, Diagnosis and Management - Rathee, Manu; Bhoria, Mohaneesh (International Journal of Medical and Health Sciences Research, 2014)
It is observed in geriatric population that a variety of changes occur with aging that can impact social, physiologic and psychological well being. Most people, however, experience a decrease or complete absence in salivary flow. Salivary dysfunction in old age is a consequence of debilitating systemic diseases and related medications, head and neck radiotherapy and reduced functional reserve that detrimentally impact nutritional status and general health. This article provides an overview on salivary gland hypofunction in geriatric population, etiopathogenesis and management strategies.